Capturing Digital Capability Readiness Among Indonesian MSMEs Actors in The Era of Pandemic COVID-19 - Aisyah Pia Asrunputri; Kurnia Budhy Scorita (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2024)
Understanding aspects related to digital capabilities will be beneficial for MSME players both in terms of technical potential and to facilitate the pace of business growth and the success of these MSMEs in the industry. Therefore, the purpose of this study is to measure digital capabilities among MSME business actors in Jakarta. This study aims to measure the readiness of MSME players in Jakarta in terms of digital capabilities in operating a business online. To analyse the data, this study used descriptive analysis. The results show that MSME players from small-sized enterprises have the highest understanding and digital capabilities compared to business actors of other types of business. The research only focusing on MSMEs players in Jakarta area, the further study needs to be established in narrower scope such as focusing on one specific industry in Jakarta area. MSME players is to invest more in digital skills that can give birth to digital innovations such as involving themselves in using digital tools such as seeing market sentiment via digital platform. This study has a unique proposition that contribute to the empirical understanding of digital capabilities readiness among MSMEs actors in Jakarta.